Impact of Listeria Inoculation and Aerated Steam Sanitization on Volatile Emissions of Whole Fresh Cantaloupes. Issue 4 (16th April 2018) - Forney, Charles F.; Fan, Lihua; Bezanson, Gregory S.; Ells, Timothy C.; LeBlanc, Denyse I.; Fillmore, Sherry
Abstract : Abstract: Rapid methods to detect bacterial pathogens on food and strategies to control them are needed to mitigate consumer risk. This study assessed volatile emissions from whole cantaloupe melons ( Cucumis melo ) as an indicator of Listeria contamination and in response to steam vapor decontamination. Cantaloupe were inoculated with Listeria innocua, a nonpathogenic surrogate for L. monocytogenes, then exposed to 85 °C steam for 240 s (4 min) followed by rapid chilling and storage for 0, 7, 10, or 14 days at 4, 7, or 10 °C. Volatile emissions from whole melons were collected on Carbopack B/Carboxen 1000 headspace collection tubes and analyzed by gas chromatography‐mass spectroscopy following thermal desorption. Introduction of L. innocua to cantaloupe rind resulted in a reduction of aromatic compound emission. However, this response was not unique to Listeria contamination in that steam vapor treatment also reduced emission of these compounds. As well, steam vapor treatment diminished the number of viable Listeria and indigenous microflora while causing physiological injury to melon rind. Heat treatment had no significant effects on flesh firmness, color, titratable acidity, or soluble solids, but the production of typical aroma volatiles during postharvest ripening was inhibited. No unique volatile compounds were detected in Listeria contaminated melons. While changes in volatile emissions were associated with Listeria inoculation, they could not be differentiated from heat treatment effects. Results indicate that volatile emissions cannot be used as a diagnostic tool to identify Listeria contamination in whole cantaloupe melons. Practical Application: The detection of pathogen contamination on fresh produce is a continuing challenge. Using a nondestructive screening method, the presence of surrogate Listeria innocua on fresh whole cantaloupes was shown to alter the emissions of aromatic volatiles from whole cantaloupes. However, these altered emissions were not found to be unique to Listeria spp. and therefore cannot be used as a definitive indicator of Listeria contamination.